2014
DOI: 10.1097/hjh.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of CPAP effect on plasma aldosterone concentration in patients with resistant hypertension and obstructive sleep apnea

Abstract: Seventy-eight patients completed the follow-up (36 CPAP, 42 conventional treatment); 58 had true resistant hypertension (74.3%), whereas 20 had white-coat resistant hypertension (25.6%). Most patients were men (70.7%), age 58.3 ± 9.4 years, and the mean apnea-hypopnea index was 50.1 ± 21.6. In patients with true resistant hypertension, CPAP achieved a significant decrease in most 24-h BP measurements and a nonsignificant decrease in PAC (25 ± 8.7 vs. 22.7 ± 9 ng/dl; P < 0.182). In patients with white-coat resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 45 publications
0
38
0
3
Order By: Relevance
“…Although several cross-sectional studies have reported a higher prevalence of non-dipping in moderate to severe OSA,12 24 only one longitudinal population-based study has reported an association between OSA and incident non-dipping of systolic BP 11. The direction of causality is further strengthened by studies that have shown CPAP therapy to lower night-time BP more than daytime BP,13 25–27 particularly in patients with resistant hypertension who are adherent to CPAP therapy 28 29. We previously reported that in the Wisconsin Sleep Cohort, total AHI severity was associated with nocturnal systolic, but not diastolic, dipping; however, that study did not attempt to differentiate between REM and NREM AHI 11.…”
Section: Discussionmentioning
confidence: 99%
“…Although several cross-sectional studies have reported a higher prevalence of non-dipping in moderate to severe OSA,12 24 only one longitudinal population-based study has reported an association between OSA and incident non-dipping of systolic BP 11. The direction of causality is further strengthened by studies that have shown CPAP therapy to lower night-time BP more than daytime BP,13 25–27 particularly in patients with resistant hypertension who are adherent to CPAP therapy 28 29. We previously reported that in the Wisconsin Sleep Cohort, total AHI severity was associated with nocturnal systolic, but not diastolic, dipping; however, that study did not attempt to differentiate between REM and NREM AHI 11.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized trials of therapeutic CPAP of up to 6 months in duration have been conducted (30,(95)(96)(97) and their collective findings presented in recent meta-analyses (98,99). The authors of a Spanish trial in which a subset (41 patients) had ambulatory monitoring confirmed drug-resistant hypertension reported a significant 10/7 mm Hg reduction in 24 hour blood pressure, a 6 mm Hg reduction in daytime diastolic blood pressure, and a greater prevalence of a 'dipping' pattern of blood pressure at night but only if CPAP was used for more than 5.8 hours nightly (97).…”
Section: Randomized Trials In Drug-resistant Hypertensionmentioning
confidence: 99%
“…Reductions in all representations of blood pressure were proportionate to CPAP use. Lloberes et al(95) allocated randomly 102 patients with both drugresistant hypertension and an AHI > 15 events/hour to CPAP or no CPAP. Of these 78 completed a 3 month follow-up.…”
mentioning
confidence: 99%
“…18 However, not all studies showed similar results; in recent RCTs 3-6 months of CPAP had no impact on BP in patients with moderate to severe OSA and resistant hypertension. 19,20 Furthermore, in an 8-week RCT with a crossover design, both CPAP and valsartan resulted in a significant reduction in mean 24-hour BP but valsartan was superior to CPAP (−7.0 mm Hg, 95 % CI −10.9 to −3.1 mm Hg; p<0.001). 21 The impact of CPAP on incident hypertension was assessed in one RCT, in which 723 patients with AHI ≥20 and ESS ≤10 were randomised to CPAP versus no CPAP.…”
Section: Impact Of Obstructive Sleep Apnoea Treatmentmentioning
confidence: 99%